Clinical-neurological differences of patients with ischemic cerebrovascular disease under and over 65 years of age - Dhara Angeline Santana Trinidad; Marisol Peña Sánchez; Sergio González García (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: The ischemic cerebrovascular disease has a high frequency due to the population aging mainly. Objective: To compare clinical characteristics of patients with ischemic cerebrovascular of two age groups. Methods: A descriptive, cross-sectional, retrospective study was carried out in the Neurology and Neurosurgery Institute in Havana, from January to December, 2017 in patients with ischemic cerebrovascular disease; 36 individuals of both age groups. In this regard, demographic variables, risk factors, clinical manifestations, coma scale and neurological deficiency, etiology and localization of the ischemic ictus were analyzed. Results: The 65 years group had a significant increase of hypertensive patients (88.9%). The average of the National Institute of Health stroke scale was superior in these patients (median [10-90 percentile]: 9.5 [4-19]). There was statistical increment of over 65 years patients with partial paralysis of the look and ataxia, but monoparesis and visual extinction in the age under 65 years. Such a scale had a statistical increase in the atherothrombotic and cardioembolic ictus in comparison with other etiologies in both patient groups. The over 65 years patients with just one risk factor or and those with hypertension had a higher punctuation of the scale. Conclusions: The degree of neurological affectation was higher in over 65 years patients that had a risk factor and in those with hypertension. As a result it could be suggested that the molecular and pathophysiolologic mechanisms of these patients vary with the age.